Arte de furtar, o oglindă a principilor? Transcendenţa textuală ca replică ironică la convenţiile unei specii literare - Laura Bădescu (Revista de Istorie și Teorie Literară)
This article highlights the textual means by which denies that the pattern of literary species could be a sufficient mark of a literary genre dedicated to the elite audience.